MICROBIOLOGICAL EVALUATION OF PASTY AND SOFT ICE CREAM - Silveira, Débora Rodrigues; de Moraes, Thamíris Pereira; Oliveira, Jannifer Scheffer; Timm, Cláudio Dias (Arquivos de Ciências Veterinárias e Zoologia da UNIPAR, 2021)
Ice creams are susceptible to contamination by handling and bad hygiene conditions during the storage process and the fraction for sale, once those can be means of diseases. This survey’s objective was to evaluate the microbiological quality of ice creams sold in bulk, of the pasty and soft types, offered for consuming. Thirty samples of pasty ice cream, sold in bulk, and thirty samples of soft ice cream were analyzed by counting thermotolerant coliforms, coagulase-positive Staphylococcus, and researching the presence of Salmonella. During the survey, were found ten (33%) samples of pasty ice cream and five (16%) samples of express ice cream out of the limits established by the Brazilian law. Salmonella was found in four samples. These results are an alert to the need of a bigger attention to the microbiological quality of ice creams, in order to ensure the consumer’s security.